Seizures in Newborn: An Update - Begum, N; Begum, T; Khatoon, S (Journal of Shaheed Suhrawardy Medical College, 2012)
Neonatal seizure is the most prominent neurological dysfunction in the neonatal period which constitutes a medical emergency. Seizures result from excessive depolarization of neurons within the nervous system. Tonic, clonic, subtle and myoclonic are the different forms of neonatal seizure. Among the causes hypoxic ischemic encephalopathy is the commonest. Jitteriness and benign neonatal sleep myoclonus should be differentiated from the neonatal seizure. Proper history taking and meticulous examination should aimed to identify the seizure and find out the aetiology. Important investigations include blood sugar, serum electrolytes (Na, Ca, Mg), arterial blood gas, anion gap, cerebrospinal fluid examination, ultrasound examination of the head and electroencephalography. Upon identification of common metabolic derangements like hypoglycaemia, hypocalcaemia, hypomagnesemia, they are treated as per recommended protocol. The rest of the symptomatic seizures (nonmetabolic) are treated with phenobarbitone. If seizures failed to respond or recur after Phenobarbitone therapy, Phenytoin, Midozolam are the subsequent options. As the recurrence rate is relatively small and the potential toxicities are high on developing brain, the good practice is to stop anticonvulsant as early as possible. Neonatal seizures have an adverse effect on neurodevelopmental outcome and predispose to cognitive, behavioral, or epileptic complications in later life. DOI: http://dx.doi.org/10.3329/jssmc.v4i1.12000 J Shaheed Suhrawardy Med Coll, 2012;4(1):26-31